Fractions of Copper in Soil and Their Contribution to Copper Availability in Rice–Wheat Cropping System under Long-Term Integrated Nutrient Management in an Acid Alfisol. Issue 8 (27th April 2016) - Sharma, Upinder; Subehia, S. K.
ABSTRACT: Long-term effects of integrated application of organics and chemical fertilizers on transformation of copper (Cu) into various chemical pools and their availability under rice ( Oryza sativa L.)–wheat ( Triticum aestivum L.) cropping system were investigated in the ongoing long-term fertilizer experiment initiated in 1991 kharif season (May–October) at the research farm of Chaudhary Sarwan Kumar Himachal Pradesh Agricultural University on an acidic soil in the Western Himalayas of India. The continuous use of chemical fertilizers alone for 20 years brought about marked depletion in all forms of copper except organically bound Cu (Cu-PYR) compared to buffer plots. Integrated use of organics and chemical fertilizers gave higher content of Cu forms over chemically treated plots except Cu occluded by free oxides (Cu-OX). Residual Cu was the most dominant form of copper contributing about 67% of the total Cu. Soil solution and exchangeable Cu (Cu-CA) was the most important fraction of copper contributing toward DTPA (diethylene triamine pentaacetic acid) extractable Cu. Content of DTPA extractable Cu increased over control when chemical fertilizers were applied in conjunction with different organics, whereas DTPA Cu content declined over control with application of chemical fertilizers alone for the last 20 years.